Pengaruh Konflik Kerja, Komunikasi Dan Lingkungan Kerja Terhadap Kinerja Karyawan ( KASUS PO Rosalia Indah Palur) - Guntoro, Fajar Andi; , Drs. Sri Padmantyo, MBA (2016)
Singer Research conducted at P.O. Rosalia Indah Palur, with Conflict of interest Influence Work, Communications and Work Environment Performance Against Employee (Case P.O. Rosalia Indah Palur) Operates individuals. Methods with study using population hearts Singer Was All employees in P.O. Rosalia Indah Palur. That amounts to 100 samples, with Samples Its taken some orangutans Singer Research hearts representing the employees. The samples Term used by 50 sample. Mechanical Sampling Sampling Method That with the retrieval using random sampling That Sampling Without picking individual That would be a member of the sample. Data Analysis Used: 1) Test Instruments (Test Validity, reliability test), 2) Classical Assumption Test (Test Heterokedasitas, Test multikolinieritas And Normality Test), 3) Multiple Linear Regression Analysis, 4) Test R2 (coefficient of determination), 5 ) Test F and 6) t test. The results of data analysis that can be TIN 1) Based on t test results showed that the value of variables tcount Conflict Of Work at -2196, Communication variables for 4579 and Work Environment variables for 7231 And Value table = 2.013, means that a singer thitung> ttabel Then Ho The influence declined so significantly Conflict Work, Communications and Environment Against Employees performance Operates individual. 2) Based on F test showed Value Fhitung 84 695, the figure Fhitung Means more than Ftabel so big decision to reject Ho. Thus Article Search Google Operating variables simultaneously Conflict Work, Communications and Environment significantly affect Performance Employee Satisfaction. Cantor showed that the influence of Conflict Work, Communications and Work Environment Performance Against Employees.